The insertion site is the main risk factor for central venous catheter-related complications in patients with hematologic malignancies - Heidenreich, Daniela; Hansen, Eleonore; Kreil, Sebastian; Nolte, Florian; Jawhar, Mohamad; Hecht, Anna; Hofmann, Wolf-Karsten; Klein, Stefan (American journal of hematology, 2022)
Central venous catheters (CVC) placed either via the internal jugular vein (IJV) or the subclavian vein (SCV) are routinely used in patients with hematologic malignancies. In this retrospective study, we systematically compared CVC-associated complications for both insertion sites, IJV and SCV. Between January 2011 and June 2013, all consecutive patients (n = 87) were included with at least one CVC (n = 153; n = 94 IJV; n = 59 SCV) at our institution due to induction/consolidation for AML/ALL or autologous hematopoietic cell transplantation (HCT). Primary study endpoints were central line-associated (CLABSI), catheter-related (CRBSI) blood stream infections and local inflammation (LI) at the insertion site. CRBSI occurred earlier and more frequently in the IJV- versus the SCV-group with an incidence rate of CRBSI at day 15 of 10% versus 0% (p = .04) and a rate of CRBSI per 1000 CVC days of 5.7 versus 1.2. In addition, CLABSI was detected more often in IJV- compared to SCV-CVC (26% vs. 8%, p = .009). Conversely, LI occurred more frequently and earlier in SCV- versus IJV-CVC (88% vs. 56%, p < .0001) with a median time to LI of 9 versus 14 days (p < .0001). The strongest risk factor for the endpoints CRBSI, CLABSI, and LI was the insertion site. However, SCV insertion was a risk factor for LI (p = .001, HR: 2.0), insertion in the IJV a risk factor for CLABSI (p = .044, HR: 2.7) and CRBSI (p = .036, HR: 5.4). These results demonstrate a differential effect of the insertion site of CVC in neutropenic patients with a significantly reduced frequency of CVC-related blood stream infections in SCV-CVC.